OGLE-2018-BLG-1428Lb: a Jupiter-mass planet beyond the snow line of a dwarf star. Issue 2 (25th February 2021) - Kim, Yun Hak; Chung, Sun-Ju; Udalski, Andrej; Gould, Andrew; Albrow, Michael D; Jung, Youn Kil; Hwang, Kyu-Ha; Han, Cheongho; Ryu, Yoon-Hyun; Shin, In-Gu; Shvartzvald, Yossi; Yee, Jennifer C; et al.
ABSTRACT: We present the analysis of the microlensing event OGLE-2018-BLG-1428, which has a short-duration (∼1 d) caustic-crossing anomaly. The event was caused by a planetary lens system with planet/host mass ratio q = 1.7 × 10 −3 . Because of the detection of the caustic-crossing anomaly, the finite source effect was well measured, but the microlens parallax was not constrained due to the relatively short time-scale ( t E = 24 d). From a Bayesian analysis, we find that the host star is a dwarf star M_host=0.43^+0.33_-0.22 M_ at a distance D_L=6.22^+1.03_-1.51 kpc and the planet is a Jovian-mass planet M_p=0.77^+0.77_-0.53 M_J with a projected separation a_=3.30^+0.59_-0.83 au . The planet orbits beyond the snow line of the host star. Considering the relative lens-source proper motion of μ _rel = 5.58 ± 0.38 mas yr^-1, the lens can be resolved by adaptive optics with a 30 m telescope in the future.